Antiviral activity of temporin-1CEb analogues against gingival infection with herpes simplex virus type 1 - Golda, Anna; Kosikowska-Adamus, Paulina; Wadowska, Marta; Dobosz, Ewelina; Potempa, Jan; Koziel, Joanna (Frontiers in Oral Health, 2024)
Oral herpes infections caused by herpes simplex virus type 1 (HSV-1) are one of the most common in the human population. Recently, they have been classified as an increasing problem in immunocompromised patients and those suffering from chronic inflammation of the oral mucosa and gums. Treatment mainly involves nucleoside analogues, such as acyclovir and its derivatives, which reduce virus replication and shedding. As drug-resistant strains of herpes emerge rapidly, there is a need for the development of novel anti-herpes agents. The aim of the study was to design an antiviral peptide, based on natural compounds, non-toxic to the host, and efficient against drug-resistant HSV-1. Here, we designed a lysine-rich derivative of amphibian temporin-1CEb conjugated to peptides penetrating the host cell membrane and examined their activity against HSV-1 infection of oral mucosa. Methods: We assessed the antiviral efficiency of the tested compound in simple 2D cell models (VeroE6 and TIGKs cells) and a 3D organotypic model of human gingiva (OTG) using titration assay, qPCR, and confocal imaging. To identify the molecular mechanism of antiviral activity, we applied the Azure A metachromatic test, and attachment assays techniques. Toxicity of the conjugates was examined using XTT and LDH assays. Results: Our results showed that temporin-1CEb analogues significantly reduce viral replication in oral mucosa. The mechanism of peptide analogues is based on the interaction with heparan sulfate, leading to the reduce attachment of HSV-1 to the cell membrane. Moreover, temporin-1CEb conjugates effectively penetrate the gingival tissue being effective against acyclovir-resistant strains. Collectively, we showed that temporin-1CEb can be regarded as a novel, naturally derived antiviral compound for HSV-1 treatment.